Parent perspectives of at-home cognitive intervention for preschoolers with Down syndrome - Walsh, Madison M., author; Fidler, Deborah, advisor; Hepburn, Susan, committee member; Yoder, Jamie, committee member (Colorado State University. Libraries, 2023)
Down syndrome (DS) is associated with challenges related to cognitive skills, including executive function (EF). Intervention provided during early childhood can support the development of EF, however there are few cognitive interventions designed for young developmental ages. Parent-mediated interventions (PMIs) are emerging as an effective and scalable intervention approach for clinical populations. PMIs require ongoing parent engagement, and therefore, it is critical for a PMI to meet the needs of its intended users. This study used a community-based participatory research (CBPR) framework to (1) understand the daily routines of families of young children with DS and (2) describe parent perceptions of participating in at-home intervention. Participants were 34 caregivers of children 3 – 6 years old with DS living in Italy or the US. Participants responded to questions related to daily tasks they help their children complete and their perceptions of at-home cognitive intervention. Interviews were transcribed and independently coded (inter-rater agreement = .80). Four themes related to daily routines were identified: what parents help with, how parents help, why parents help, and how children respond. Three themes related to parent perceptions of interventions were identified: advantages of parent-led interventions, disadvantages of parent-led interventions, and desires for interventions. Findings suggest that PMIs targeting preschool-aged children with DS should require a short time commitment, blend intervention activities into daily routines, and include other family members. Findings from this study have important implications for the development of novel interventions aimed at supporting families in this population.
Keywords: Down syndrome; focus groups; children; intervention; executive function